PEMASARAN MELALUI KONTEN DI TIKTOK UNTUK MENDUKUNG PERTUMBUHAN UMKM - Selma Salsabila; Isnawijayani; Desy Misnawati; Moh. Hafizni; Isnawijayani Isnawijayani (Bajang Institute, 2025)
The digital era has brought significant changes to marketing strategies, particularly in the culinary sector. The use of social media has become a key factor in introducing products, building brand image, and increasing sales. This study aims to analyze the role of content creators in developing culinary businesses in Palembang through the implementation of viral marketing and personal branding strategies. This research employed a qualitative method with a case study approach. Data were collected through in-depth interviews with business owners and content creators, observation of promotional activities on social media, and documentation of published content. The findings reveal that content creators play an important role in expanding market reach, increasing brand awareness, shaping positive perceptions, and fostering greater audience engagement. The applied viral marketing strategies successfully triggered interactions, built trust, and influenced consumers’ purchasing decisions. Furthermore, social media platforms such as TikTok, Instagram, and YouTube proved effective as promotional tools with wide reach and relatively low cost compared to conventional advertising. These findings indicate that the involvement of content creators can be a driving factor in enhancing the competitiveness of culinary MSMEs, especially for business owners with limited promotional resources. In conclusion, creative, well-planned, and consistent digital strategy management can have a significant positive impact on business growth